Whose Disability? A Centrifugal Quest to Confront the Stereotypical Views on ‘Disability’ - Rakshit, Shankha Shekhar; Mukherjee, Sumedha (JOURNAL OF INDIAN EDUCATION, 2023)
The word ‘disability’ is generally associated with a negative connotation, i.e., ‘the lack of ability to do something.’ But it is not necessarily true in all circumstances. The level of disability of a person does not always determine the limitations of their activities. Many people have succeeded in their lives overcoming their difficulties by proving themselves as differently abled in such activities which are supposed to be impossible due to their disability on those contexts. But every human being should realise the potency or ability of those people who have the power to fight against any adverse situation. So, our paper aims at analysing in detail the stories of success of the so-called disabled people. The quest of the paper is to find out how the people with physical deformities have challenged and surpassed the notion of common people regarding disabilities.